Dysregulation of the Scribble/YAP/β‐catenin axis sustains the fibroinflammatory response in a PKHD1−/− mouse model of congenital hepatic fibrosis. Issue 6 (20th May 2022) - Fabris, Luca; Milani, Chiara; Fiorotto, Romina; Mariotti, Valeria; Kaffe, Eleanna; Seller, Barbara; Sonzogni, Aurelio; Strazzabosco, Mario; Cadamuro, Massimiliano
Abstract: Congenital hepatic fibrosis (CHF), a genetic cholangiopathy characterized by fibropolycystic changes in the biliary tree, is caused by mutations in the PKHD1 gene, leading to defective fibrocystin (FPC), changes in planar cell polarity (PCP) and increased β‐catenin‐dependent chemokine secretion. In this study, we aimed at understanding the role of Scribble (a protein involved in PCP), Yes‐associated protein (YAP), and β‐catenin in the regulation of the fibroinflammatory phenotype of FPC‐defective cholangiocytes. Immunohistochemistry showed that compared with wild type (WT) mice, in FPC‐defective ( Pkhd1 del4/del4 ) mice nuclear expression of YAP/TAZ in cystic cholangiocytes, significantly increased and correlated with connective tissue growth factor (CTGF) expression and pericystic fibrosis, while Scribble expression on biliary cyst cells was markedly decreased. Cholangiocytes isolated from WT mice showed intense Scribble immunoreactivity at the membrane, but minimal nuclear expression of YAP, which conversely increased, together with CTGF, after small interfering RNA (siRNA) silencing of Scribble. In FPC‐defective cholangiocytes, inhibition of YAP nuclear import reduced β‐catenin nuclear expression, and CTGF, integrin β6, CXCL1, and CXCL10 mRNA levels, whereas inhibition of β‐catenin signaling did not affect nuclear translocation of YAP. Notably, siRNA silencing of Scribble and YAP in WT cholangiocytes mimics the fibroinflammatory changes of FPC‐defective cholangiocytes. Conditional deletion of β‐catenin in Pkhd1 del4/del4 mice reduced cyst growth, inflammation and fibrosis, without affecting YAP nuclear expression. In conclusion, the defective anchor of Scribble to the membrane facilitates the nuclear translocation of YAP and β‐catenin with gain of a fibroinflammatory phenotype. The Scribble/YAP/β‐catenin axis is a critical factor in the sequence of events linking the genetic defect to fibrocystic trait of cholangiocytes in CHF.